Conquering Carbs - Petrie, Kristin (Edina, MN ABDO Publishing, 2004)
Discusses the different types of carbohydrates, which foods provide them, how the body uses them, and their importance in a healthy diet.
Elementary
Keywords: Carbohydrates; Nutrition